Development of Teaching Material Supplements Based on Socio Scientific Issues to Improve Students' Scientific Argumentation Ability - Anam, Khairul; Bintari, Siti Harnina; Parmin, Parmin (Universitas Negeri Semarang, 2023)
The impact of the Covid-19 pandemic has touched every aspect of people's lives, including health and education. Because there is a lot of ignorance about prevention of Covid-19, it is necessary to have learning media that is easily accepted. E-Books are one of the solutions to provide education about the SARS CoV-2 virus which is given to students as a supplement to teaching materials on viruses. The purpose of this study was to test the validity of teaching steel supplements as learning media on viruses and students' scientific argumentation skills. This research uses the Thiagarajan 4-D model development method (Define, Design, Develop, Disseminate). The data analysis technique used is descriptive data analysis including the validity of responses from users and the effectiveness of the products tested on class X MIPA 1 student of SMAN 1 Bandar Lampung. The results showed that the developed e-book had valid criteria by material experts with a score of 75.00% and very valid by media experts with a score of 95.83%. Students and teachers responded to the e-book used in learning, respectively 92.17% and 94.38% with very valid criteria. Analysis of students' scientific argumentation abilities showed moderate criteria with an average N-gain value of 0.52. Thus, the teaching material supplement in the form of an e-book that is being developed can be used as a biology learning medium to improve students' scientific argumentation skills.